Misguided negative adaptation narratives are hurting the poor: Measurement and maladaptation are being weaponized - Schipper, Lisa; Mukherji, Aditi (American Association for the Advancement of Science, 2024)
Since publication of the Intergovernmental Panel on Climate Change (IPCC) Working Group II report in 2022, adaptation has been gaining attention among decision-makers and practitioners, including on the international policy level through the United Nations Framework Convention on Climate Change (UNFCCC). Two dimensions of adaptation in particular have received considerable focus: the risk of maladaptation, and the contention that any metrics to assess success are likely to fall short of capturing all dimensions of adaptation. Although these conclusions are grounded in academic evidence, problems arise when policy-makers interpret such findings in overly simplistic ways with possible negative implications on adaptation finance and implementation. As two IPCC authors who contributed to scientific narratives of the risks of adaptation, we argue that weaponizing maladaptation and claiming that adaptation success is impossible or unmeasurable as excuses to reduce or halt funding is not grounded in the latest science and ends up hurting vulnerable communities.